“Optional” “ergativity” in Tibeto-Burman languages - DeLancey, Scott (2024)
The case-marking systems of Tibeto-Burman languages are a long standing problem in both synchronic description and analysis and historical reconstruction. Early research on the family tended to characterize the family, and especially the Tibetan languages, as ergative. But work over the last two decades has demonstrated, first with respect to Tibetan, and then to other languages of the family, that the prevalent “alignment” is a “pragmatic ergative” pattern in which a case marker is optionally present on A and some S arguments of the clause. The “optional” presence of the ergative marking is determined by semantic factors, especially agentivity and perfectivity, and pragmatic factors, particularly contrast. It is now clear that this grammatical phenomena characterizes the family as a whole, although there are a few languages which show more familiar typological profiles.